Mediating Effect of Self-Efficacy in Pain Management between Knowledge and Attitude of Pain toward Pain Management Practice among Nurses in Indonesia - Herry Susanto; Tzu-Ying Lee (lppm Universitas Muhammadiyah Semarang, 2024)
Nurses' knowledge and attitudes significantly influence pain management practices. Higher levels of self-efficacy in pain management are associated with improved pain. This study explored the relationships between nurses' knowledge and attitudes toward pain, self-efficacy in pain management, and actual pain management practices. This study employed a cross-sectional study which conducted at Sultan Agung Islamic Hospital, Indonesia, involving 249 nurses selected based on predefined criteria. Participants responded to an online survey encompassing demographic queries and standardized tools, namely the Knowledge and Attitude Survey Regarding Pain (KASRP-IDN), the Pain Management Self-Efficacy Questionnaire (PMSEQ-IDN), and the Nurse Behavior Questionnaire in Pain Management (NBQ-P). Mediation analysis was further conducted using the PROCESS add-on to discern the mediating effect of self-efficacy in pain management between knowledge and attitude of pain toward pain management practice among nurses. The study showed significant positive relationships among Knowledge and Attitude Survey Regarding Pain (KASRP), Pain Management Self-Efficacy (PMSE), and Pain Management Practice. However, the mediation analysis depicted that self-efficacy exerted a relatively modest mediating effect between KASRP and pain management practice (K2=0.17, CI= 0.05-0.27). The findings manifest the positive associations between knowledge-attitude regarding pain, self-efficacy in pain management, and pain management practices among nurses. In the future, in-service programs related to pain management should increase the nurses' knowledge and attitude and enhance their confidence, resulting in actual practice in pain management. However, the mediation effect of self-efficacy is modest, indicating the plausible existence of other contributory variables or factors warranting further exploration and elucidation.